Belajar gramatika sambil berpuisi: kenapa tidak? - Bukhori, Herri Akhmad; Rofi'ah, Rofi'ah (2020)
This paper describes the use of German Poetry as a way to master the structure of German Language and learners' perceptions about it. It is a qualitative study that has been supported by quantitative data. The first data was the use of German Poetry in the German Language Class which has been collected through observation, while the second data were learners perceptions about the use of poetry to master German language structure which has been collected through questionnaire. The study shows that poetry is able to be used in the class as one of the ways to master German language structure. In addition, the learners have a positive mind about this way of learning and they find that it helped them mastering particular German language structure. They were having fun and most of them even would use it again in the class.